The analysis of principal conditions of van Oss-Chaunhury-Good’s method in investigations of surface layers of polymeric materials - Żenkiewicz, M. (Polimery, 2022)
The selected problems related to investigations of surface layers (WW) of solids were presented. The analysis of essential limits of van Oss-Chaunhury-Good’s (vOCG) method, used for calculation of surface free energy (SEP) of polymeric materials, has been done. Some reasons of discrepancy between the results of calculations, obtained by various authors, were discussed in details. Namely, the need of use of algebraic analysis for selection of the set of three measured liquids, which are necessary in vOCG method, has been pointed. It makes possible to eliminate the sets of liquids being the reasons of bad conditioning of the sets of equations for SEP calculation. The effect of the proper selection of scale of components (acidic and basic ones) of SEP of water on the right evaluation of selected properties of the materials investigated was also presented (Table 1&2). General conclusions concerning the causes of controversy over van Oss-Chaunhury-Good’s method were formulated.